Transformasi Pendidikan Bisnis di Era Digital: Analisis Studi Pustaka - Mutmainah; Ristiana, Ina; Rokimin (LP2M IAIN Sultan Amai Gorontalo, 2026)
Digital transformation has brought significant changes in various aspect of life, including higher education, particularly in business education. The transformation of business education in the digital era has become a necessity to address the increasingly complex and dynamic global challenges. The shift in the learning paradigm from conventional methods to digital requires adjustments in the curriculum, teaching methods, and the competencies of both lecturers and students to remain relevant to the needs of business and industry. The purpose of this literature review is to identify and synthesize existing literature on the adoption of digital technology in business education, as well as its impact on the curriculum, teaching methods, and learning outcomes. The methodology used in this study is a qualitative approach with a library research method, analyzing recent research from various journals, books, and scholarly articles. The main findings indicate that digital transformation provides broad access to education, more interactive learning, and improved digital competencies for students, although challenges such as resistance to change and limited infrastructure remain. This study concludes that a holistic and sustainable strategy for implementing digital transformation is crucial, including digital competency training for educators and the development of adequate information technology infrastruktur. Recommendations focus on strengthening collaboration between educational institutions, business practitioners, and technology developers to support adaptive and innovative business education in the digital era.